The Spiral Code: Modeling the Morphogenetic Fingerprint of Life - Samuel Desta Alemu (Britain International for Academic Research (BIAR) Publisher, 2014)
Natural morphologies, from phyllotactic spirals in sunflowers to logarithmic nautilus shells, embody efficient parametric geometries governed by irrational angles like the golden ratio (φ ≈ 1.618) and superformulas. These patterns optimize packing, growth, and structural integrity, inspiring biomimicry amid escalating demands for sustainable engineering by 2005. Purpose: This study synthesizes mathematical modeling of Fibonacci phyllotaxis, logarithmic spirals, L-systems, and superformulas to validate natural patterns, evolve biomimetic designs via genetic algorithms, and quantify performance in solar arrays, antennas, and composites. Evolutionary algorithms (population=200, generations=50) optimized parameters across morphospaces, integrated with FEA for structural metrics and ray-tracing for efficiency. Findings: Golden-angle phyllotaxis achieved 95% packing density, nautilus fits yielded b=0.31 (MSE=4.14), pinecone divergences α=142.3° (HD=0.20). Superformula morphospaces spanned m=1-8, n1=0.5-3.0, evolving b from 0.08 to 0.124 (+55%).